Molecular Mechanisms for Adhesion and Colonization of Human Gastric Mucosa by Helicobacter pylori and its Clinical Implications - Coelho, Elisabete; Magalhães, Ana; Dinis-Ribeiro, Mário; Reis, Celso A. (Acta Médica Portuguesa, 2016)
Introduction: Helicobacter pylori infection is very prevalent worldwide and is associated with the progression of the gastric carcinogenesis cascade, being one of the main risk factors for the development of gastric carcinoma. Several factors are determinant for the infection and for the development of gastric disease, including environmental factors, host genetic factors and virulence factors of the bacteria. Material and Methods: In this review, we present an overview of the current knowledge on the determinants of the infection and on the recently described molecular mechanisms of Helicobacter pylori adhesion to the gastric mucosa, as well as its possible future therapeutic application. Results: The adhesion of Helicobacter pylori to the gastric epithelium is critical for gastric pathogenesis, allowing bacterial access to nutrients and the action of bacterial virulence factors, promoting recurrence of the infection and the progression of the gastric carcinogenesis pathway. Discussion: Eradication of Helicobacter pylori infection is the best preventive strategy available against gastric cancer, mainly if it is achieved before the development of pre-neoplastic lesions. The increase in antibiotics resistance, together with the eradication failures in some patients, has promoted the development of alternative treatments. Conclusion: The new therapeutic strategies, focused on the molecular mechanism of Helicobacter pylori adhesion, are very promising; however, future studies are needed to evaluate its in vivo efficiency and toxicity.